Sistema de creencias en relación al cannabis, su uso y consecuencias: consumidores versus no consumidores de una población de universitarios colombianos (2023)
Descriptive and comparative study of cross-sectional that had as objective to evaluate and compare the beliefs about cannabis, its use and potential consequences between two groups of Colombian university students, matched by gender and age. The frst group consisted of ordinary consumers of cannabis (n=35) the second group consisted of students that have never tried cannabis (n=35). The results showed that the group of consumers presents a moderate risk of abuse and only the 20% fulflled dependence criteria. Furthermore, the non-consumers group was mostly agree about that the marijuana use: damages the memory, deteriorates the cognitive functions, creates dependency, can affect the neurons and mental health. Also, it can lead to legal problems, it is a harmful drug for the health, it affects the academic performance, it creates problems with the family, friends, couple and the like, it reduces the driving ability, and, that the marijuana that is sold in the street is always pure. The consumer group, instead, agreed that smoking tobacco affects the lungs more than smoking marijuana. Marijuana has a positive in?uence on the brain, it increases the creativity, and it is less damaging than alcohol and tobacco. Smart people smoke marijuana and it has medicinal effects. In conclusion, according to the kind of beliefs that they have about this drug, the cannabis consumers would have a decreased perception of risk in relation to the potential risk that the consumption brings from two points of view: a. They minimize the real risks of consuming and, b. They attribute some benefts and virtues to the cannabis. The kind of beliefs that the consumer have are maybe in?uenced, at least, in part, for experiences of family and other consumers and, furthermore, the reinforcement of the same consume.